2018
DOI: 10.3758/s13415-018-0582-8
|View full text |Cite
|
Sign up to set email alerts
|

Neurocognitive mechanisms behind emotional attention: Inverse effects of anodal tDCS over the left and right DLPFC on gaze disengagement from emotional faces

Abstract: Our findings support a lateralized role of left and right DLPFC activity in enhancing/worsening the top-down regulation of emotional attention processing. These results support the rationale of new therapies for affective disorders aimed to increase the activation of the left over the right DLPFC in combination with attentional control training, and identify specific target attention mechanisms to be trained.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
43
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 56 publications
(50 citation statements)
references
References 36 publications
6
43
0
1
Order By: Relevance
“…The data show a difference in dilation due to real versus placebo stimulation, denoting an adjustment in sympathetic nervous system in response to tDCS. Prior studies using excitatory NIBS over the right DLPFC showed adverse effects on emotional attention (e.g., increased attention towards negative stimuli, reduced attentional control over emotional information; [14,41,[58][59][60]), which in turn is suggested to contribute to maladaptive emotion regulatory processes [42,61]. These findings would be consistent with the notion that excitatory right DLPFC stimulation contributes to decreased cognitive resource allocation to process emotional information, impeding individuals' capacity to engage in emotion regulatory processes.…”
Section: Discussionsupporting
confidence: 78%
See 2 more Smart Citations
“…The data show a difference in dilation due to real versus placebo stimulation, denoting an adjustment in sympathetic nervous system in response to tDCS. Prior studies using excitatory NIBS over the right DLPFC showed adverse effects on emotional attention (e.g., increased attention towards negative stimuli, reduced attentional control over emotional information; [14,41,[58][59][60]), which in turn is suggested to contribute to maladaptive emotion regulatory processes [42,61]. These findings would be consistent with the notion that excitatory right DLPFC stimulation contributes to decreased cognitive resource allocation to process emotional information, impeding individuals' capacity to engage in emotion regulatory processes.…”
Section: Discussionsupporting
confidence: 78%
“…Research in healthy volunteers showed that anodal (i.e., excitatory) tDCS over the left DLPFC decreased emotional reactivity towards negative stimuli, as measured by both behavioral [11,12], and psychophysiological [13] assessment methods. To date, even though NIBS is optimal to study lateralization of DLPFC in emotional processing, research in healthy populations is currently limited to the scope of selective emotional attention [14]. Specifically, it has been shown that anodal (i.e., excitatory) tDCS over the right DLPFC leads to diminished emotional attentional disengagement, whereas anodal tDCS over the left DLPFC leads to improved emotional attentional disengagement.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Namely, when individuals are trained to regulate their emotional attention, anodal tDCS over the lDLPFC improves looking towards or away from negative stimuli [47,48]. Similarly, when the task requires looking away from emotional faces, anodal tDCS over the lDLPFC reduces the time to disengage gaze from emotional faces [49]. In addition, for individuals with major depression, anodal stimulation over the lDLPFC reduces the interference from emotional stimuli in a working memory task [50].…”
Section: Introductionmentioning
confidence: 99%
“…For example, Andrews et al (2011) and Martin et al (2013) demonstrated that left DLPFC tDCS (contralateral supraorbital and extracephalic cathode respectively) delivered with concurrent cognitive training results in significantly improved working memory performance compared with tDCS or cognitive training alone. Anodal tDCS to the left, but not the right DLPFC (contralateral supraorbital cathode) has also been shown to facilitate goal-directed cognition in the form of facilitated attentional disengagement from emotional content (Sanchez-Lopez et al, 2018).…”
Section: Introductionmentioning
confidence: 99%